Supine ergometry for aged population with degenerative mitral regurgitation: evidence for prognostic yield. (3rd October 2022) - Armenis, I; Demerouti, E; Motsi, A; Kyrzopoulos, S; Tsiapras, D; Athanassopoulos, G
Abstract: Introduction: Degenerative mitral regurgitation (MR) has an increased prevalence with aging with risk stratification evolving as a complex scenario. Semisupine bicycle ergometry (SBE) is a currently applied means to interrogate noninvasive hemodynamics. Aim: Aim of the study was to interrogate prognostic parameters by SBE in asymptomatic moderate to severe degenerative MR for patients older than 65 years. Patients and methods: One hundred seventy-four asymptomatic MR patients (pts), followed up on valve clinic in a tertiary center (age 56/14 female 71), were referred for SBE. MR related cardiac events (surgery, NYHA worsening) during follow up of 34/25 months occurred in 24 pts. Age group >65 had 53 pts (age 71/4 vs 50/13 <0.001, females 36% vs 43%). The following parameters (mean/SD) were estimated at rest (R) and SBE (Ex): Biplane left ventricular (LV) ejection fraction (EF), stroke volume (SV), 2D LV strain (SR), tricuspid peak gradient (TRpg), transmitral E/e, HR, systolic blood pressure (SBP), HR*SBP product and their respective % changes (%d). Results: Group >65 during SBE had a decreased workload (Watts: 74/22 vs 89/18, p<0.001), similar % achieved target heart rate (73/11 vs 69/10), with more symptoms (30% vs 16%, p<0.01). Event rate was greater (30% vs 7%, p<0.001). Group aged>65 had differences in SBPR (145/20 vs 132/19, p<0.002), SREx (20/4 vs 21/5, p<0.04), EFEx (64/9 vs 68/6, p<0.01), TRpgR (34/11 vs 27/6, p<0.001), TRPG Ex (55/13 vs 50/10, p<0.02), E/eEx (14/6 vs 11/3, p<0.006), %dSV (0.01/0.23 vs 0.14/0.25, p<0.001) and %dEF (0.12/0.08 vs 0.15/0.11, p<0.03). In stepwise logistic regression analysis for events, E/eEx was the only selected (log exp 0.89, p<0.05). Classification for events by ROC analysis gave a E/eEx cut off 13 (area 0.67, p=0.01) with sensitivity/specificity 50/80%. Kaplan Meier analysis revealed prognostic contribution for E/eEx >13 only in the age >65 (log rank p<0.04, Figure 1). Moreover, symptomatic SBE had a decisive prognostic contribution in the aged cohort (Kaplan-Meier log rank = 0.004, Figure 2). Conclusion: SBE may be applied with an efficient performance in the older then 65 years age spectrum, within the context of asymptomatic moderate to severe degenerative MR, providing critical information for risk stratification Funding Acknowledgement: Type of funding sources: None.